The influence of the real estate market on the economic development of Constanța County - Stan, Mari-Isabella (Technium Social Sciences Journal, 2022)
At the local level, the promotion of sustainable economic development by creating a favorable business development climate and new employment opportunities is necessary to increase the well-being and development of communities. The economic and social mechanism of the real estate market guides economic agents’ activity, being influenced by its relationship with other sectors of the economy, such as construction, trade, tourism, the financial banking system and, last but not least, the management of local public administrations, which allow the development of various types of investment projects. The aim of this article is to carry out an analysis from a dynamic perspective of the real estate market at the level of the economic agents in Constanța County, which operate in the field of real estate transactions, showing how their economic effects influence local development. The results of this research show that companies in the real estate transactions sector, together with the construction sector, play an important part in the development of the local economy, and that there is a positive relationship between the real estate market and the construction market.